2020
DOI: 10.3390/molecules25133019
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Korean Red Ginseng Polysaccharides in Aged Rat Using Global Proteomic Approach

Abstract: Much has been written on the physiological benefits of Korean Red Ginseng (KRG). Among its various components, ginsenosides have been widely investigated for their various pharmacological effects. However, polysaccharides are a major KRG component that has not received scrutiny similar to that of ginsenosides. The present study aims to fill that gap in the existing literature and to investigate the possible functions of polysaccharide in KRG. The researchers evaluated proteomic changes in non-saponin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Here, RGAP groups showed significantly increased AFCs in all groups dose dependently compared to the immunosuppressed CY control. Lee et al [ 43 ] studied KRG polysaccharides’ immune effects, and their results showed increased AFCs compared to the negative control. The present study shows that phagocytosis activity significantly increased compared to the CY control in all doses of RGAP groups.…”
Section: Resultsmentioning
confidence: 99%
“…Here, RGAP groups showed significantly increased AFCs in all groups dose dependently compared to the immunosuppressed CY control. Lee et al [ 43 ] studied KRG polysaccharides’ immune effects, and their results showed increased AFCs compared to the negative control. The present study shows that phagocytosis activity significantly increased compared to the CY control in all doses of RGAP groups.…”
Section: Resultsmentioning
confidence: 99%
“…Relative to the cyclophosphamide model group, the cytotoxicity and proportion of NK cells in the whole blood, and the levels of expression of perforin and granzyme in the NK cells in the Cy + low-dose GP and Cy + high-dose GP groups enhance significantly [ 44 ]. The non-saponin fractions with rich polysaccharides of red ginseng also show immune-promoting activity, which in turn increases plasma cell count in the spleen and inhibits the melanoma lung metastases in rats [ 45 ]. In combination with the αPD-1 monoclonal antibody (mAb) (250μg/mouse), GPs significantly increase the ratio of CD8+/CD4+ T cells in the spleen, blood, and tumor tissues of mice, along with an increase in the production of functional cytokines, including IFN-γ, TNF-α, and GZMB.…”
Section: Mechanisms Underlying the Antitumor Effects Of Gpsmentioning
confidence: 99%
“…Similarly, NFP, which is a polysaccharide from Korean red ginseng, inhibited melanoma cell metastasis to the lung, which may have resulted due to its immunity-enhancing effect [ 91 ]. Furthermore, a polysaccharide from ginseng leaves, GS-P, promoted macrophages and natural killer (NK) cells to exhibit anti-metastatic activity against colon cancer [ 92 ].…”
Section: Biological Activities Of Different Polysaccharides From the Three Speciesmentioning
confidence: 99%